Benign lymphoepithelial cyst - Habib, Saequa; Rahman, Md Mustafizur; Choudhury, A Allam; Kamal, Mohammed (Bangladesh Journal of Otorhinolaryngology, 2010)
Benign lymphoepithelial cyst, also known, as branchial cyst is an infrequent lesion usually occurs in the parotid gland or the lateral cervical area including lymph nodes. It occurs due to the process of lymphocyte-induced cystic ductular dilatation and is always diagnosed postoperatively by histopathological examination. The cyst is usually lined by squamous epithelium surrounded by lymphoid stroma. Although unusual, two cases diagnosed within two months are reported here. Both patients were male but the locations of the lesions were different. One lesion was within cervical lymph node and the other was near the parotid gland. Both the lesions were surgically excised and diagnosed histopathologically as benign lymphoepithelial cyst. Its frequent association with HIV infected patients since last two decades has made it a significant lesion now-a-days. In this regard along with reported two cases brief literature reviews including origin, diagnosis and treatment are discussed. Key words: Benign lymphoepithelial cyst; parotid; lymph node; HIV infected patients. DOI: 10.3329/bjo.v16i1.5783 Bangladesh J Otorhinolaryngol 2010; 16(1): 60-65